(untitled) (Research, Society and Development, 2021)
This work aimed to verify if there is a passage, as a cultural heritage, of knowledge about medicinal plants from generation to generation in rural communities, if the inhabitants of communities in the Northeastern semi-arid region already had any knowledge about the properties of the jucá (C. ferrea), and whether, based on this prior and cultural knowledge, they would accept to use this plant as a natural disinfectant. For this purpose, interviews were conducted in 388 residences, where each residence was interviewed by only one person, from October 2017 to September 2018, conducted in eight traditional communities in the municipality of Mossoró-RN (Cordão de Sombra 1 and 2, Hipólito 1 and 2, Independence, Solitude, Hair of Nêgo and Três Marias). As a result, it was found that 54.4% (197) were over 50 years old, 64.1% (230) were female and that 77% (278) of the interviewees had lived in the traditional community for more than 10 years. Regarding the knowledge of the medicinal activities of the jucá, it was observed that 81.5% (295) claimed to have knowledge about the medicinal activity of the jucá, 53.9% (195) stated that they had already used the jucá in people as alternative medicine and 93, 3% (362) would accept to use the disinfectant based on the jucá. Thus, it is evident that the use of jucá as a disinfectant would be well accepted and used by the population, as a result of which it has already been used for other therapeutic purposes by residents of traditional communities around Mossoró/RN.